Identification of guano magnetic mineral types from Bau Bau cave in East Kalimantan, using x-ray diffraction (XRD) - Dolla Yuliza Pertama (Department of Physics – Universitas Negeri Padang UNP, 2014)
The existence of minerals magnetic guano can be identified by knowing the kind of the minerals magnetic contained in guano. This research is to identification the kind of minerals-magnetic-guano from Bau-Bau Cave, East Kalimantan. The kind of minerals magnetic are Identified using X-Ray Diffraction (XRD). Kind Minerals magnetic is determined by comparing the measured data with database of minerals. The measurement results showed that the guano samples have a mineral magnetic content. Kind of minerals magnetic in guano is magnetite (Fe3O4), it can be seen from the pattern at XRD measurements fractions. Data analysis showed that there are minerals magnetic in guano, it is happen because minerals magnetic transport from environments in to the cave